Uji Peran Moderasi Masa Kerja Dalam Hubungannya Dengan Praktek-Praktek MSDM Dan Produktivitas Kerja - Fernandy Fernandy (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the practice of human resource management which consists of: HR planning, recruitment, training and development, compensation, performance management, employee relations with employee work productivity and working period moderation in relation to MSDM practices and work productivity. This research uses quantitative research methods. data collection using research instruments, data analysis is quantitative or statistical. The sample used in this study were 50 employees who have worked at least 1 year and live in Yogyakarta. The sampling technique was convenience sampling. The data collection method in this research is a questionnaire method (questionaire). Data analysis used multiple linear regression analysis and moderate regression analysis (moderate regretion analysis). The results showed that (1) HR Planning has a positive and significant effect on Work Productivity, (2) Recruitment has a positive and significant effect on Work Productivity, (3) Training and Development has a positive and significant effect on Work Productivity, (4) Compensation has a positive and significant effect on Work Productivity. significant impact on work productivity (5) performance management has a positive and significant effect on productivity and (6) Relationships between employees have a positive and significant effect on work productivity and tenure can strengthen the relationship between HR practice and work productivity with a value of 98.2% Keywords: Role Test, Service Period, HRM, Work Productivity